1987
DOI: 10.1021/ja00236a029
|View full text |Cite
|
Sign up to set email alerts
|

Chemometrics of solvent basicity: multivariate analysis of the basicity scales relevant to nonprotogenic solvents

Abstract: 483present. This is consistent with the longer S-N bonds to these two nitrogens.One of the most striking features in 7 is the short S--0 "nonbonded" distance of 2.55 A. Although this distance is clearly much longer than a nominal S-0 bond distance of 1.70 A (sum of covalent radii), it is clearly much shorter than the sum of the van der Waals radii of (3.25 A).37 There is, then, a reasonably strong interaction between the S+ and the 0, probably an electrostatic polarization of the oxygen lone pairs by the catio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(65 citation statements)
references
References 4 publications
2
63
0
Order By: Relevance
“…[71,72] Indeed, the estimated decrease in the lone pair occupancy (n (N) ), from acetonitrile to pyridine and to trimethylamine, is followed by a significant increase in the HF antibonding s* population (s* (HF) ), due to the increase in the interaction energy (E ð2Þ n!s * ). On the other hand, when the nature of the accepting group is kept constant, such as in the substituted pyridines 22, 23 and 33, there is a good proportionality between the electrostatic and the covalent contributions to the hydrogen-bond attractive energy as previously suggested by Maria et al [73] As shown in Figure 3B, the plot between pK HB and D ðHFÞ 0 values also presents separate lines corresponding to families but with slightly better statistics. The marked difference Table 4.…”
supporting
confidence: 69%
“…[71,72] Indeed, the estimated decrease in the lone pair occupancy (n (N) ), from acetonitrile to pyridine and to trimethylamine, is followed by a significant increase in the HF antibonding s* population (s* (HF) ), due to the increase in the interaction energy (E ð2Þ n!s * ). On the other hand, when the nature of the accepting group is kept constant, such as in the substituted pyridines 22, 23 and 33, there is a good proportionality between the electrostatic and the covalent contributions to the hydrogen-bond attractive energy as previously suggested by Maria et al [73] As shown in Figure 3B, the plot between pK HB and D ðHFÞ 0 values also presents separate lines corresponding to families but with slightly better statistics. The marked difference Table 4.…”
supporting
confidence: 69%
“…10 The enthalpic changes of complexation to boron trifluoride are dependent on the solvent and appear in the order: DMF > THF > CH 3 CN > CH 3 NO 2 > CH 2 Cl 2 . 11,12 This analysis is in agreement with our observation that the top three solvents relatively stabilize Lewis acids and thus the resulting reactions either do not proceed at all, or proceed very slowly. Nitroalkanes have low coordinating ability probably due to resonance and we selected 1-nitropropane for further studies because this solvent afforded the best yield (80%).…”
Section: Effects Of Solvent and Lewis Acid On Glycosylationsupporting
confidence: 87%
“…By the method of principal component analysis (PCA), Maria, Gal et al [184] determined the dimensionality of basicity scales, affinity scales and spectroscopic scales of basicity. They studied a data matrix of 22 neutral oxygen and nitrogen bases and 10 scales.…”
Section: A Chemometric Approachmentioning
confidence: 99%